Some Properties of \(ε\)-Kenmotsu Manifolds With Quarter-Symmetric Non-Metric Connection - Singh, Abhishek; Gautam, Sangeeta; Kumar, Lalit (Communications in Mathematics and Applications, 2024)
The objective of this paper is to investigate the \(ε\)-Kenmotsu manifolds with quartersymmetric non-metric connection. We have investigate an \(ε\)-Kenmotsu manifolds admitting the quarter-symmetric non-metric connections satisfying certain conditions. We have further provided the equivalent conditions for Ricci soliton in an \(ε\)-Kenmotsu manifolds to be shrinking or expanding with the quarter-symmetric non-metric connection. We have also investigated \(φ\)-projectively flat, Quasiprojectively flat and some interesting results. Finally, we have given an example of 3-dimensional \(ε\)-Kenmotsu manifolds with respect to quarter-symmetric non-metric connection.
Keywords: (ϵ)-Kenmotsu manifold; Quarter-symmetric non-metric connection; Ricci soliton; Quasiprojectively flat; φ-projectively flat